Uncle Shelby's story of Lafcadio, the lion who shot back - Silverstein, Shel (HarperCollins, 1963)
After leaving the jungle for the circus and a life of fame and wealth, a lion who taught himself to be the best shot in the world discovers he's not really a lion anymore, and not really a man, either.